Upaya Peningkatan Potensi Ekonomi Sanggar Sapu Jagat Desa Teluk Pinang melalui Pelestarian Budaya Pencak Silat dalam Perspektif Islam - Nurmayanti, Nurmayanti; Ramdhani, Nina Krisna (Neolectura, 2024)
Sanggar Sapu Jagat is a studio located in Teluk Pinang Village, Ciawi District, Bogor Regency, which has a Pencak Silat cultural heritage. Pencak Silat is a cultural heritage that has historical values, martial arts and spiritual values in the Islamic tradition. From an Islamic perspective, Pencak Silat can be understood as a form of physical and mental training that is in line with the concepts of balance and discipline. By utilizing this cultural heritage wisely, we can achieve economic gain while still upholding spiritual values and local wisdom that are in line with Islamic teachings. In its development, currently Sanggar Sapu Jagat is experiencing a very significant economic decline from year to year. There are many problems that occur, one of which is the interest of the people of Teluk Pinang Village in preserving Pencak Silat culture. This causes the economic income generated from this studio to decrease. Therefore, efforts are needed to improve the economy of Sanggar Sapu Jagat. According to the Big Indonesian Dictionary, Edition III 2003, effort is an attempt to achieve a goal, solve a problem and find a way out. In this journal, researchers have a program to increase the economic income of Sanggar Sapu Jagat by making a Pencak Silat Documentary Short Film which will then be uploaded on social media. However, to fulfill these efforts, support is needed from the government, related institutions and the community in maintaining and developing to achieve sustainable results.